INFLUENCE OF PROFIT AND CASH FLOW ON FINANCIAL DISTRESS CONDITIONS - Refsianty Hayyu Juliani; Asep Muslihat (Jurnal Ilmu Manajemen Profitability, 2021)
Food and Beverage Company is the mainstay company of the manufacturing industry therefore creating strong competition that occurs in it. Companies that are unable to compete and improve their performance will experience financial difficulties and eventually head into bankruptcy. This research aims to find out how much influence profit and cash flow have on the Financial Distress of food and beverage companies listed on the Indonesia Stock Exchange in 2014-2019. The research method used is verification descriptive with a quantitative approach. The results of the verification analysis state that partial return on assets is influential and significant to financial distress. Meanwhile, cash flow indicates that cash flow (operating cash flow ratio) has a negative and significant financial distress. Simultaneously, profit and cash flow accounted for 41.7% of financial distress while the remaining 58.3% was explained by other variables beyond the multiple regression equations or those not studied in this study